(untitled) (International Journal of Physiotherapy, 2015)
Background: It’s a well-known fact that exercise is good for the mind and body making it beneficial for expectant and new mothers. The challenge of pregnancy, labor and looking after a new born is not an easy task. So the fitter you are the better you will cope with this life changing event. Method: Aerobic and strengthening exercises help in adjusting to the increasing weight and posture changes to cope effectively with the labor and the postnatal period. Although exercises in pregnancy are extremely beneficial, they can cause more harm than good if not done correctly. Medical screening for exercise should be done by the Doctor as well as the Physiotherapist to ensure that the patient underwent a basic screening, assessment or continued monitoring for the right exercise protocol for avoidance of any complications and to ensure the benefits of staying healthy and fit. Results: Evidence shows that exercise training programs designed and delivered by the Physiotherapists can relieve the prenatal post natal problems. Conclusion: Number of studies has shown the positive effects of aerobic and strengthening exercises on pregnant women. The physical changes to a pregnant woman’s body are multiple. There are center of mass changes, pressure on the organs and increased weight gain. In fact, over two thirds of pregnant women experience back pain, one fifth experience pelvic pain and over 40% experience urinary incontinence in their first pregnancy.